Stage-specific distribution models can predict eel (Anguilla anguilla) occurrence during settlement in coastal lagoons - LEONE, CHIARA; CAPOCCIONI, FABRIZIO; GRAVINA, MARIA FLAVIA; CICCOTTI, ELEONORA; Zucchetta, M; Franzoi, P (Estuarine, Coastal and Shelf Science, 2016)
Eel (Anguilla anguilla) is a catadromous fish species typical of Mediterranean coastal lagoons, that currently suffers from several anthropogenic and natural impacts. These are thought to be the cause of a stock-wide decline that this panmictic species is facing, in inland and coastal waters of Europe and North Africa. The decline affects both adult phases and recruitment, i.e. glass eel arrival to coastal waters and their ascent to inland waters. Quantitative features of eel recruitment reflect a transoceanic global scale, but also depend on local environmental conditions, the latter also affecting settlement dynamics in transitional waters. There is only little information on the dynamics of these two processes in coastal lagoons, notwithstanding the paramount importance of both in sustaining local stocks abundance and their demographic structure for this typical but also economically important inhabitant of Mediterranean lagoons, habitats that constitute an important share of the eel distribution area. The present study aims, therefore, to clarify space and time dynamics of local scale recruitment and of settlement in a coastal lagoon in the Mediterranean area, also by setting up a specific methodological approach. For this purpose, data from field surveys in combination with Species Distribution Models (SDMs) have been used in order to relate distribution of eel juvenile stages to the environmental conditions within the lagoon. Specifically, models were calibrated to quantify the relationship between presence of juvenile eel and the main environmental drivers, with the aim of identifying potential habitats for eel settlement within the lagoon. Results gained by modelling suggest certain spatial and temporal colonization patterns for the juvenile eel in the Fogliano lagoon, a typical Mediterranean coastal lake. The modelling approach has therefore proved to be a useful tool for predicting habitats for eel recruitment at the local scale and settlement, because adequate to catch the spatio-temporal dimensions ...